2017
DOI: 10.4067/s0718-07642017000600010
|View full text |Cite
|
Sign up to set email alerts
|

Accesibilidad e Integración Digital: Elementos Clave para un Programa de Formación de Empresarios en Empoderamiento Digital

Abstract: *Autor a quien debe ser dirigida la correspondenciaRecibido Dic. 15, 2016; Aceptado Ene. 6, 2017; Versión final Mar. 13, 2017, Publicado Dic. 2017 Resumen El objetivo de este trabajo es proponer un Programa de Formación para el empoderamiento digital de administradores de micro, pequeñas y medianas empresas (MiPymes). Para ello, se indaga en las competencias en tecnologías de información y comunicación (TIC) que poseen los administradores de MiniPymes. Bajo una metodología de investigación-acción, se encuestar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
2
0
4
Order By: Relevance
“…These results indicate that in the MSMEs of Guanajuato in Mexico, they have a better degree of digital readiness compared to the MSMEs in Colombia, according to the study by Martelo, Jiménez and Jaimes (2017), although they have the challenge of continuing to advance in the incursion of e-commerce, as well as incorporating ICT such as integral systems, design through software, networks without a central server, specialized systems such as ERP, CRM, among others, if they intend to stay in the market and handle the economic crisis they are facing, where the challenge is to reinvent yourself to survive.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These results indicate that in the MSMEs of Guanajuato in Mexico, they have a better degree of digital readiness compared to the MSMEs in Colombia, according to the study by Martelo, Jiménez and Jaimes (2017), although they have the challenge of continuing to advance in the incursion of e-commerce, as well as incorporating ICT such as integral systems, design through software, networks without a central server, specialized systems such as ERP, CRM, among others, if they intend to stay in the market and handle the economic crisis they are facing, where the challenge is to reinvent yourself to survive.…”
Section: Discussionmentioning
confidence: 61%
“…However, incorporating ICT is not easy for MSMEs, due to their shortcomings in obtaining and managing resources, requiring technological preparation of human capital, facilitating accessibility in ICT and transferring decision making power to the company's Human Capital, through the empowerment strategy. In the literature, there are few studies on ICT accessibility (Martelo, Jiménez & Jaimes, 2017), with no studies found to link the empowerment of human capital as an influencing factor in the degree of e-Readiness, technological preparation of human capital and ICT accessibility. In addition, the degree of ICT readiness is an area that deserves further investigation, in accordance with what is established by Golding, Donaldson, Tennat and Black (2008), especially since the use of ICT is reflected in the company size and sector, and there is a tendency to increase the use of ICT as their size increases (Pérez, Ramírez, and Topete, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, se han desarrollado diferentes trabajos que indagan cuáles son las competencias más desarrolladas y las principales necesidades que las empresas presentan de cara a mejorar el empoderamiento digital. Por ejemplo, los peores resultados en las micro, pequeñas y medianas empresas según Martelo et al (2017) son la baja experiencia en el comercio electrónico, la ausente retroalimentación con el cliente, la baja formación en el área técnica, entre otros aspectos. Por el contrario, sí que se hace un uso de las TIC para la gestión interna de la empresa y se dispone en general de una adecuada infraestructura tecnológica (página web, correos, redes sociales o programas informáticos actualizados).…”
Section: Competencias Claveunclassified
“…Según Martelo et al (2017), las empresas deben hacer uso intensivo de las tecnologías de la información y la comunicación (TIC) para la gestión interna de su negocio, y es común contar con una infraestructura tecnológica adecuada (sitio web, correo electrónico, redes sociales o programas informáticos actualizados). Por lo anterior, el uso de una página web en la empresa Teleperformance para el área Telecom-ACD es de vital importancia porque permite acceder a múltiples recursos como el correo empresarial, plataformas virtuales y bases de datos, servicios que en la actualidad se encuentran muy dispersos en distintas plataformas informáticas de la empresa, esto debido a que la optimización de procesos permite tener un mejor desempeño y resultados para la organización (Tocto Esteban, 2011).…”
Section: Introductionunclassified